Reliving the Past for Recreating the Present in Margaret Atwood's Selected Poems - Al-Wattar, Shaymaa Zuhair (Al-Adab Journal, 2019)
For centuries poets tend to utilize the past in their poetry, however their approaches are various. The Canadian icon and phenomenal poet and novelist Margaret Atwood's approach is unique as she revise while others simply retell past stories. She delves deeply into the rich past, reliving its stories whether it was taken from myths, history, or fairy tales, revising them to present a new version of the old stories, but this time from women's perspective. She invested heavily in the past to recreate something new, something that is going to make the present liveable and to fortify the future.Her literary oeuvre is rich with revised poems. The poems usually tackle serious issues that affect the lives of women. She chooses the victimized muted misrepresented female protagonists, those who were silenced and subjugated by patriarch society, revising them and endows them with voices, awareness, power, free-will and autonomous identity. Reliving the past and recreating of the gendered prescribed roles is a means of survival that will help women to properly live the present and ensure a better future.